Pesantren Technology-Friendly: Enhancing Learning Effectiveness in The Modern Era - Muhammad Najihul Huda; Zulkarnain; Syarof Nursyah Ismail; Auwalu Shuaibu Muhammad (Nadwa: Jurnal Pendidikan Islam, 2025)
This research explores the integration of technology in Islamic boarding schools (pesantren) and its influence on learning effectiveness in the modern era through a Systematic Literature Review (SLR) combined with content analysis, examining data from accredited academic journals. The findings indicate that technology enhances pesantren learning through innovations such as e-learning platforms, digitization of kitab kuning (classical Islamic texts), modern administrative tools, and expanded da’wah outreach while facilitating collaborations with external institutions to strengthen infrastructure. However, challenges such as limited technological resources, low digital literacy, and concerns about the negative impacts of technology on students’ character persist. To address these issues, pesantren adopt strategies including digital literacy training, collaboration with external partners, the establishment of internal regulations, and a moderated approach to technology use, ensuring technological advancements align with Islamic values. This study contributes by providing a framework for balancing tradition and modernity, offering practical insights for policymakers and educators to optimize technology use in pesantren, empowering students to thrive in a globalized and interconnected world while preserving their cultural and religious essence.